Physical activity of parents and of their children: a systematic review of Brazilian sample studies – Report Card Brazil - Tebar, William R. [UNESP]; Oliveira, Crystian B.s. [UNESP]; Gil, Fernanda C.s. [UNESP]; Saraiva, Bruna T.c. [UNESP]; Suetake, Vinicius Y.b. [UNESP]; Scarabottolo, Catarina C. [UNESP]; Delfino, Leandro D. [UNESP]; Fernandes, Romulo A. [UNESP]; Christofaro, Diego G.d. [UNESP] (Universidade Federal de Santa Catarina, 2018)
The aim of this study was systematically review the researches in regard the association of PA of parents and the PA of their children. A literature search was performed in five databases (Medline, Embase, Cinahl, Lilacs and SciELO) using combined terms about youth, PA and social support, with restriction to publications with Brazilian sample and to English and Portuguese language. Thirteen studies were included in this review and was observed a positive association of parental PA and the PA of their children for the majority of the studies (n=11). Only two studies did not observed significant association between PA of parents and their children and, otherwise, it was not observed negative associations in the review. It was observed different associations according to the gender of both parents and children. This findings support the importance for the practice of PA by parents as encouragement for the practice of PA by their children among Brazilians. The strategies to promote the increase in practice of physical activity of children and adolescents of both genders may consider the social support as an important factor, especially in relation to the practice of PA of their parents.

O objetivo do presente estudo foi revisar sistematicamente estudos que analisaram a associação da prática de atividade física de pais e filhos. Foi realizada uma busca sistemática em cinco bases de dados (Medline, Embase, Cinahl, Lilacs e SciELO), por meio da combinação de termos sobre crianças e adolescentes, atividade física e suporte social, sendo restrita a estudos contendo amostras brasileiras e escritos em Inglês e/ou Português. Foram incluídos treze estudos na presente revisão e foi observada associação positiva da prática de atividade física de pais e filhos na maioria dos estudos (n=11). Somente dois estudos não observaram associação significativa da atividade física de pais e filhos, contudo não foram observadas associações negativas. Foram observadas diferentes associações de acordo com o gênero tanto dos pais quanto dos filhos. Estes achados ressaltam a importância da prática de atividade física dos pais como incentivo à prática de atividade física dos filhos em amostras brasileiras. Estratégias de promoção da prática de atividade física em crianças e adolescentes de ambos os sexos devem considerar o suporte social como um fator importante, especialmente a respeito da prática de atividade física dos pais.
Atividade física de pais e filhos: uma revisão sistemática de estudos com amostras brasileiras – Report Card Brazil
Keywords: Adolescent; Child; Parents; Physical activity; Social support; Adolescente; Apoio social; Atividade física; Criança; Pais